UTANG LUAR NEGERI (ULN) PEMERINTAH RI: BERMANFAAT ATAU MENYENGSARAKAN? - Purnomo, Didiet (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2003)
This article tries to explain the impact of Indonesian government foreign debt on its economic condition. The debt, on one hand, especially one through the government course is badly hoped to return Indonesian economic condition to be better after crisis. On the other hand, however the government foreign debt accumulation becomes the boomerang for Indonesian government. How far is actually the permissiveness of the foreign loan can be clarified via some approaches i.e. budget principle, net transfer. and Debt Service Ratio (DSR) approaches. The visible phenomenon based on the above approaches illustrates that Indonesian government foreign debt condition is hugely accumulated, so it is regarded to exceed the repayment power.